The association between periodontal disease and age-related macular degeneration in the Korea National health and nutrition examination survey: A cross-sectional observational study. Issue 14 (April 2017) - Shin, Yong Un; Lim, Han Woong; Hong, Eun Hee; Kang, Min Ho; Seong, Mincheol; Nam, Eunwoo; Cho, Heeyoon
Abstract : Abstract: Periodontal disease (PD) is associated with various systemic diseases. We investigated the association between PD and age-related macular degeneration (AMD). For this population-based, cross-sectional study, we enrolled 13, 072 adults at least 40 years of age with gradable retinal fundus photographs and community periodontal index (CPI) data from the Korean National Health and Nutrition Examination Survey (KNHANES) (2008–2010 and 2012). Participants were divided into a middle age group (age ⩽62 years) and old age group (age >62 years). PD was divided into 2 categories of mild and severe. Logistic regression analysis was used to evaluate the association between PD and AMD (early and late). The prevalence of PD and AMD in the study population was 37.4% ± 0.8% and 5.6% ± 0.2%, respectively. Overall, there was no significant difference in the proportion of participants with PD between those with and without AMD. Only participants with AMD in the middle age group had more any PD than those without AMD ( P  = 0.031). Multivariate logistic regression model after adjusting for all confounding factors showed that PD was not significantly associated with AMD (odds ratio [OR] 1.03, 95% confidence interval [CI] 0.86–1.22). However, according to degree of PD, participants with severe PD in the middle age group were 1.61 times more likely to have AMD (OR 1.61, 95% CI 1.02–2.54). Our data, collected from an Asian population, showed that only severe PD is independently associated with AMD in individuals aged 62 years or younger.